Pengaruh Konsentrasi Kadmium Terhadap Perubahan warna Dan Persentase Jenis Kelamin Jantan Anakan Daphnia magna [Influences Concentration Of Cadmium To Colour Change And Male Sex Percentage Neonates Daphnia magna] - Rahayu Kusdarwati; Alfi Hermawati W; Setyawati Sigit; A. Shofy Mubarak (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract Cadmium is one of dangerous heavy metal and it can cause water pollution. As an alternative early warning toward heavy metal in water, Daphnia magna can be used as biology indicator water pollution that caused by heavy metal. Daphnia magna is organism that ussualy used for bioassay in many progressing countries, because that organism have important role in freshwater ecology, short life cycle about 3 weeks and sensitive toward chemical environment. Grade of toxicity heavy metal can measured with lethal and sub lethal parameter. In Daphnia magna, sub lethal parameter that can be observe are colour changes and male sex percentage neonates. The purpose of this research was to know the colour changes and male sex percentage neonates Daphnia magna in different concentration of cadmium. Target of this research is to gets information about level colour changes and male sex percentage neonates Daphnia magna in different concentration of cadmium. The main parameter was colour changes and male sex percentage neonates and the secondary parameters were water quality (temperature, pH, dissolved oxygen and NH3) The result of research of giving different cadmium concentration to the adult female Daphnia magna not showing significant influence, nevertheless it is showing significant influence toward male sex percentage neonates Daphnia magna. The treatment with cadmium concentration 0,0004 mg/l produce 100% male neonates Daphnia magna. Water quality during research were in optimal conditions to support Daphnia magna life, those are temperature 26°C, pH range from 8,0 – 8,2 and dissolve oxygen (DO) range from 8,5 – 9,0 mg/l and ammonia 0 – 0,03 mg/l.